A new species of Aspidistra (Asparagaceae) from Guizhou, China - Xu, Wen-Fen; Wang, Yong; He, Shun-Zhi (Phytotaxa, 2015)
In October 2008, an investigation at the Guizhou province, Guiding County, Pingfa township found some low and small plants of Aspidistra Kew Gawler (1822: 628) with freshly opened flowers widespread in the limestone valley. After investigations in the wild for several years (30 September 2010, 13 October 2011, 16 October 2014) were performed, this species was identified as new for science after studying relevant literature.